Epigenetic Mechanisms in the Transcriptional Regulation of Circadian Rhythm in Mammals - Wei Mao; Xingnan Ge; Qianping Chen; Jia-Da Li (Biology)
Almost all organisms, from the simplest bacteria to advanced mammals, have a near 24 h circadian rhythm. Circadian rhythms are highly conserved across different life forms and are regulated by circadian genes as well as by related transcription factors. Transcription factors are fundamental to circadian rhythms, influencing gene expression, behavior in plants and animals, and human diseases. This review examines the foundational research on transcriptional regulation of circadian rhythms, emphasizing histone modifications, chromatin remodeling, and Pol II pausing control. These studies have enhanced our understanding of transcriptional regulation within biological circadian rhythms and the importance of circadian biology in human health. Finally, we summarize the progress and challenges in these three areas of regulation to move the field forward.